2020
DOI: 10.3389/fimmu.2020.587581
|View full text |Cite
|
Sign up to set email alerts
|

Granzyme B in Inflammatory Diseases: Apoptosis, Inflammation, Extracellular Matrix Remodeling, Epithelial-to-Mesenchymal Transition and Fibrosis

Abstract: Inflammation is strictly interconnected to anti-inflammatory mechanisms to maintain tissue homeostasis. The disruption of immune homeostasis can lead to acute and chronic inflammatory diseases, as cardiovascular, pulmonary, metabolic diseases and cancer. The knowledge of the mechanisms involved in the development and progression of these pathological conditions is important to find effective therapies. Granzyme B (GrB) is a serine protease produced by a variety of immune, non-immune and tumor cells. Apoptotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 109 publications
(182 reference statements)
1
54
0
Order By: Relevance
“…Granzyme B can amplify the death signal by inducing cytochrome c release. It can also activate caspase-3 directly [24].…”
Section: Perforin/granzyme Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Granzyme B can amplify the death signal by inducing cytochrome c release. It can also activate caspase-3 directly [24].…”
Section: Perforin/granzyme Pathwaymentioning
confidence: 99%
“…Therefore, in these types of pathways, signaling pathways that are upstream are bypassed and execution phase of apoptosis is directly influenced. It is suggested that both the mitochondrial pathway and direct activation of caspase-3 are critical for granzyme B induced killing activates both mitochondrial pathway and caspase-3 activation [24,25]. The immune cells that express highly variable and regulated patterns of granzymes include natural killer (NK) cells, cytotoxic CD4 and CD8 T cells, and regulatory T cells (Tregs).…”
Section: Perforin/granzyme Pathwaymentioning
confidence: 99%
“…Perforin makes the pore in the cell targeted membrane up to 20 nm in diameter and initiates cytotoxic molecules entering into the cytoplasm [ 44 ]. Granzyme B is a serine protease that initiates cell apoptosis in a perforin-dependent manner produced by cytotoxic cells [ 45 ]. Granzyme B cleaves and activates various caspases, such as caspases 3 and 7, which trigger cell apoptosis [ 45 ].…”
Section: Clinical Sign and Biomarker For Drug Eruptionmentioning
confidence: 99%
“…Granzyme B is a serine protease that initiates cell apoptosis in a perforin-dependent manner produced by cytotoxic cells [ 45 ]. Granzyme B cleaves and activates various caspases, such as caspases 3 and 7, which trigger cell apoptosis [ 45 ]. Granzyme B also has many substrates in the nucleus, leading to DNA disruption.…”
Section: Clinical Sign and Biomarker For Drug Eruptionmentioning
confidence: 99%
“…Elevated granzyme levels are also detected in the circulation in many diseases, including autoimmune diseases, atherosclerosis, pulmonary diseases, but also during infection or inflammation (15)(16)(17). Increasing evidence is emerging that granzymes exert noncytotoxic extracellular functions in inflammation, extracellular matrix degeneration, and wound healing (18)(19)(20). GrK is expressed by macrophages and plays a pathogenic role in inflammation, reepithelialization, and matrix remodeling during wound healing (21).…”
Section: Introductionmentioning
confidence: 99%